Not Just a Gender Numbers Game: How Board Gender Diversity Affects Corporate Risk Disclosure - Seebeck, Andreas; Vetter, Julia (Journal of Business Ethics, 2021)
This paper examines how board gender diversity affects corporate risk disclosure. We exploit an exogenous shock on firms’ risk environment created by the United Kingdom’s vote to leave the European Union (Brexit) and analyze related risk disclosure in annual reports of public firms in the UK. Using this unique setting, we mitigate concerns about omitted variables in concurrent studies. The findings suggest that board gender diversity is positively related to corporate risk disclosure. However, our results also indicate that the proportion of female directors needs to reach a critical mass to impact the risk disclosure decision. Moreover, we find lower bid–ask spreads immediately after the referendum date for those firms that disclosed Brexit-related risks in their annual reports prior to the vote. Collectively, our results are consistent with board gender diversity promoting the disclosure of decision-relevant information through improved board group dynamics.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Board gender diversity; Brexit referendum; Corporate risk disclosure; Critical mass theory; Information asymmetry; Gender